Use of a gene expression system based on potato virus X to rapidly identify and characterize a tomato Pto homolog that controls fenthion sensitivity. - Rommens, C M (1995)
A novel transient gene expression system was used to study both the tomato disease resistance gene Pto and a Pto homolog designated Fen. The gene expression system was based on potato virus X (PVX). Tomato plants that were both susceptible to strains of Pseudomonas syringae pv tomato carrying the corresponding avirulence gene avrPto and insensitive to the insecticide fenthion were infected with in vitro-generated transcripts of PVX derivatives containing either Pto or Fen. Expression of the Pto gene from the virus genome failed to elicit P.s. tomato resistance, indicating that the PVX system is not suitable for the study of Pto. However, expression of the Fen gene resulted in sensitivity to fenthion. The utility of the PVX gene expression system was further demonstrated through structure/function studies of the Fen gene. A correlation was shown between Fen protein kinase activity and the ability of this protein to confer fenthion sensitivity to tomato. Furthermore, it was demonstrated that mutation of a putative N-terminal myristoylation site, proposed to be involved in membrane targeting, rendered the Fen protein inactive. Analysis of a Pto-Fen chimeric gene allowed the fenthion sensitivity domain to be localized to the C-terminal part of the Fen protein. Interestingly, expression of the Fen kinase from the PVX genome in Nicotiana spp resulted in a fenthion-independent necrotic response. Our results support the involvement of the Fen gene in a signal transduction pathway(s).